P270 Identification of responder groups to fluticasone furoate/vilanterol (ff/vi) in the salford lung study in copd (sls copd) using a cluster analysis model. (15th November 2017) - Nicholls, A; Bakerly, N Diar; Collier, S; Dickinson, H; Leather, D; Boucot, I
Abstract : Background: Identifying patients who respond more favourably to specific therapy allows for optimal disease management (maximising treatment benefits; minimising treatment-related risks) and better allocation of limited healthcare resources. SLS COPD, a 12 month, open-label, randomised controlled trial conducted in UK primary care, compared the clinical effectiveness and safety of initiating once-daily inhaled FF/VI 100/25 µg versus continuing usual care (UC) in patients with COPD. The trial met its primary effectiveness endpoint demonstrating an 8.4% reduction in the mean annual rate of moderate/severe exacerbations with FF/VI versus UC (95% CI: 1.1–15.2; p=0.02; primary effectiveness analysis population). 1 Aim: Identify patient subgroups demonstrating an enhanced response with FF/VI versus UC in SLS COPD, using a cluster analysis approach. Methods: This exploratory post-hoc analysis utilised a data-driven recursive partitioning algorithm (SIDES 2 ) to identify several candidate patient subgroups, each with the potential to demonstrate added benefit of FF/VI versus UC compared with the parent intent-to-treat (ITT) population, based on the primary effectiveness endpoint. Twenty-four distinct patient variables were considered, including baseline demographics, COPD history and disease characteristics, comorbidities, socioeconomic status and treatment adherence. Following identification of a "best" candidate subgroup, the primary effectiveness model used in the original SLS COPD study 1 was repeated to evaluate the potential additional benefit of FF/VI versus UC in this subgroup. Results: Eight candidate subgroups were identified, defined by combinations of coronary artery disease (CAD) diagnosis, CAT TM score, age and polypharmacy. The subgroup indicating the greatest potential treatment effect of initiating FF/VI versus continuing UC comprised 1430/2799 (51%) ITT patients with no CAD diagnosis, baseline CAT score ≤33 and age ≥61 years. In this subgroup, the mean annual rate of moderate/severe exacerbations was reduced by 21.40% (95% CI: 12.79–29.17) with FF/VI versus UC, contrasting with the observed reduction of 8.4% (95% CI: 1.4–14.9) in the overall ITT population. 1 Conclusions: The identified patient subgroup demonstrated an enhanced response with FF/VI versus UC compared to the overall SLS COPD population. Work is ongoing to validate/confirm these findings in an alternative COPD dataset. Funding: GSK (HZC115151/NCT01551758 ). Please refer to page A260 for declarations of interest in relation to abstract P270. References: . Vestbo Jet al. NEJM 2016;375:1253–60. . Lipkovich Iet al. Stat Med2011;30:2601–21.